تحليل الأخطاء في القراءة لدى طلاب الفصل الثاني الدراسي عام 2024\2025في قسم تعليم اللغة العربية بجامعة شريف هداية الله الإسلامية الحكومية جاكرتا - Amanullah, Akhdan Ariq Amanullah; Wati Susiawati (Penerbit Minhaj Pustaka, 2025)
This study aims to analyze common reading errors in Arabic texts among second-semester students of the Arabic Language Education Department at the Faculty of Educational Sciences, Syarif Hidayatullah State Islamic University Jakarta for the 2024/2025 academic year. It is an applied case study focusing on two textbooks: al-‘Arabiyyah al-Muyassarah and al-Ājurrūmiyyah. A qualitative approach using a case study method was employed, involving a purposive sample of 49 students. Data were collected through observation, interviews, and document analysis, ensuring rich triangulation. Error analysis followed Abdul Raqhi’s framework, which includes identifying, describing, interpreting, and correcting errors. Influencing factors were examined using the Miles and Huberman model, involving data reduction, display, and conclusion drawing. The findings revealed 24 types of errors, with 431 occurrences. The most common was related to weak verbs (71 times, 16.47%), followed by errors in subject structure (59 times, 13.69%), and indefinite nouns (35 times, 8.12%). Other errors included adjective structure (51 times), subject-verb agreement (32), and predicate structure (24). The study recommends reinforcing the contextual teaching of Arabic grammar and morphology, increasing practice with vocalized texts, and applying error analysis as an effective strategy to enhance students’ reading skills.